(untitled) (ex æquo, 2013)
The essay explores how silence represents a «feminine language» that communicates through a non-uttered voice. The analysis of silence is here conducted in performance art practice by focussing on the work of Guatemalan artist Regina José Galindo: by using her works, the essay shows how the artist bears witness to trauma and to gender-related violence. This investigation approaches silent performance as capable of articulating and triggering both ethical and political considerations.